Effect of Essential Oil from Lippia origanoides on the Transcriptional Expression of Genes Related to Quorum Sensing, Biofilm Formation, and Virulence of Escherichia coli and Staphylococcus aureus - Andrés Martínez; Elena E. Stashenko; Rodrigo Torres Sáez; German Zafra; Claudia Ortiz (MDPI AG, 2023)
Microbial infections resistant to conventional antibiotics constitute one of the most important causes of mortality in the world. In some bacterial species, such as Escherichia coli and Staphylococcus aureus pathogens, biofilm formation can favor their antimicrobial resistance. These biofilm-forming bacteria produce a compact and protective matrix, allowing their adherence and colonization to different surfaces, and contributing to resistance, recurrence, and chronicity of the infections. Therefore, different therapeutic alternatives have been investigated to interrupt both cellular communication routes and biofilm formation. Among these, essential oils (EO) from Lippia origanoides thymol-carvacrol II chemotype (LOTC II) plants have demonstrated biological activity against different biofilm-forming pathogenic bacteria. In this work, we determined the effect of LOTC II EO on the expression of genes associated with quorum sensing (QS) communication, biofilm formation, and virulence of E. coli ATCC 25922 and S. aureus ATCC 29213. This EO was found to have high efficacy against biofilm formation, decreasing-by negative regulation-the expression of genes involved in motility (fimH), adherence and cellular aggregation (csgD), and exopolysaccharide production (pgaC) in E. coli. In addition, this effect was also determined in S. aureus where the L. origanoides EO diminished the expression of genes involved in QS communication (agrA), production of exopolysaccharides by PIA/PNG (icaA), synthesis of alpha hemolysin (hla), transcriptional regulators of the production of extracellular toxins (RNA III), QS and biofilm formation transcriptional regulators (sarA) and global regulators of biofilm formation (rbf and aur). Positive regulation was observed on the expression of genes encoding inhibitors of biofilm formation (e.g., sdiA and ariR). These findings suggest that LOTCII EO can affect biological pathways associated with QS communication, biofilm formation, and virulence of E. coli and S. aureus at subinhibitory concentrations and could be a promising candidate as a natural antibacterial alternative to conventional antibiotics.